SCIENCE NATURE VOL. 2(1), PP.42-89, MARCH 2019 (FULL MAGAZINE) - science nature (SCIENCE NATURE, 2019)
This Volume 2, Issue 1 is the second issue of SCIENCE NATURE which had been scheduled to be online on 13rd March 2019. The theme of this particular issue was about actions for better health with a new discovery of golobe (Zingeberaceae fruit) from Seram, Maluku province, Indonesia named as Elim alliacea, a new genus [1] of the golobe ever found absolutely different from former amonum and hornstedtia genus, respectively. The contributed papers were only 5 best from 2 different countries authors of Indonesia, and America. The total numbers of paper were 47 pages plus 13 Science Nature Devotions including the first certificate of excellence given to Prof. Long. Y. Chiang as one of the editorial board in Boston, USA on 22nd March 2019. Reference [1]. H.I. Elim, Science Nature Vol. 1, Issue 1, pp. 66-70 (2019).